Static magnetic field attenuates lipopolysaccharide-induced multiple organ failure: A histopathologic study in mice. (February 2015) - Lai, Wei-Yi; Huang, Yu-Chih; Chang, Wei-Jen; Wang, Hsin-Ta; Fong, Tsorng-Harn; Lin, Che-Tong; Huang, Haw-Ming
Abstract: Purpose : Previous studies demonstrated that static magnetic fields (SMF) were effective in down-regulating the expression of lipopolysaccharide (LPS)-induced inflammatory cytokines. The aim of this study was to provide histological evidence of SMF attenuating LPS-induced multiple organ failure (MOF). Materials and methods: In this study, BALB/cByJNarl (5 weeks, weighing 20–25 g) mice were chosen as test subjects. The tested animals were challenged with 50 mg/kg LPS after they were exposed to a continuous SMF for 2 h. The survival rate and pathological changes in lungs, kidneys, and livers of the LPS- challenged mice were examined with and without SMF treatment. In addition, the effects of SMF exposure on body temperature control of the LPS-challenged mice were monitored. Results : Our results showed that at 30 h the survival rate of LPS-challenged mice increased 3.6-fold ( p < 0.05). In addition, 6 h after LPS injection, the average body temperature of SMF-exposed mice was 1.07°C lower than that of unexposed animals. Tissue biopsies demonstrated that SMF exposure reduced damage to the lungs, livers, and kidneys in the LPS-challenged mice. Conclusions : SMF show potential as a viable prophylactic alternative for controlling LPS-induced MOF.